Clinical study of Rh-isoimmunization in pregnant women - Bhagat, Bhavani; Sitalakshmi, V.; Azad, K. L.; Banoth, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Iso-immunization has been defined as the process whereby immune antibodies are produced in an individual in response to antigens from another individual of same species. Objective was to study the fetal outcome in immunized and non-immunized women and also to prevent isoimmunization during pregnancy and labour. Methods: A total of 40 patients attending outdoor antenatal clinic or admitted in the indoor wards in obstetric unit of Obstetrics and Gynecology department were included in the present study which was hospital based cross sectional study. The study was carried out for one year at Government Medical College Jagdalpur, Chhattisgarh, India. Permission from Institutional Ethics Committee was obtained. From each and every patient included in the study, initially informed individual consent was taken. Results: Maximum patients (25%) had an income of Rs. 200- 300 per month and minimum patients (10%) had an income of Rs. 500- 600 per month. Maximum cases of Rh – negative patients 87.5% are Hindus and 10 % are Muslims while only 2.5% are Christians. The percentage of patients below 20 years is 2.5, that between 20 to 25 are 67.5, between 26 to 30 is 27.5 and between 31 to 35 is 2.5. Thus, maximum patients belong to the age group 20 to 25 years and above 31 years.. Accordingly, 6 patients had history of abortion, 2 had pre- term deliveries, and 18 had full term deliveries. 4 had history of operation and 1 had history of jaundice in previous children. Cases with presence of Rh- Antibody in Maternal Circulation during Pregnancy. It was found that one out of 40 patients, had Rh- Antibody in titer of 1: 128 and 39 cases, did not show presence of Rh- Antibody in their circulation. Outcome of pregnancy in 40 patients studied. 3 patients had pre- mature labour, 26 had normal vaginal delivery, 10 had caesarean section and one patient was Ante- natal. Conclusions: Present study reveals more than Maximum patients were from low socioeconomic group and minimum cases were from higher socio- economic group. Majority of cases were Hindus, next in order Muslims and then Christians. Age of maximum patients ranged from 20-25 years. Maximum patients had normal full term deliveries. In 65% cases, outcome of pregnancy was normal vaginal delivery.